2007
DOI: 10.1002/ibd.20126
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 receptor (IL-23R) gene protects against pediatric Crohnʼs disease

Abstract: Background-The IL-23 receptor (IL-23R) has been found to be associated with small bowel Crohn's disease (CD) in a whole genome association study. Specifically, the rare allele of the R381Q single nucleotide polymorphism (SNP) conferred protection against CD. It is unknown whether IL-23R is associated with IBD in children. The aim was to examine the association of IL-23R with susceptibility to IBD in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 13 publications
10
72
2
1
Order By: Relevance
“…3 Here, we report that an uncommon coding variant of the IL-23R (1142G4A) confers strong protection against the occurrence of severe acute GVHD after transplant as it has been already shown for inflammatory bowel disease recently by Duerr and coworkers and others. 10,11 The protective effect of the IL-23R gene variant on acute GVHD occurred primarily when the gene variant …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Here, we report that an uncommon coding variant of the IL-23R (1142G4A) confers strong protection against the occurrence of severe acute GVHD after transplant as it has been already shown for inflammatory bowel disease recently by Duerr and coworkers and others. 10,11 The protective effect of the IL-23R gene variant on acute GVHD occurred primarily when the gene variant …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Recently, a gene variant of the interleukin-23 receptor (IL-23R-1142G4A) was found to be strongly associated with Crohn's disease. 10,11 IL-23 is a new member of the IL-12 family that plays a critical role in promoting inflammatory responses mediated by type 1 helper T cells. IL-23 and IL-12 share same molecule structure.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed genetic characterization VE Garcia et al diseases including IBD (particularly adult and pediatric Crohn's disease), [16][17][18][19][20][21][22][23][24] AS, 25,26 and GO. 27 It is possible that IL23R variants also underlie susceptibility to celiac disease, 28 Graves' disease without ophthalmopathy 27 and multiple sclerosis, 28,29 although the evidence is not currently strong for celiac disease and Graves' disease without opthalmopathy and is contradictory for multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 These results have been verified in four independent studies [12][13][14][15] and have paralleled association studies in related diseases. One of the IL23R missense SNPs implicated in psoriasis, R381Q, has also been strongly associated with several autoinflammatory phenotypes: several studies have found R381Q-mediated predisposition to adult inflammatory bowel disease (IBD), especially Crohn's disease [16][17][18][19][20][21] and pediatric Crohn's disease in individuals of European descent, [22][23][24] two sizable studies reported association of multiple IL23R SNPs with ankylosing spondylitis (AS) 25,26 and a North American study demonstrated IL23R susceptibility for Graves' ophthalmopathy (GO). 27 IL23R polymorphisms have also been studied in celiac disease with mildly significant results 28 and multiple sclerosis with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of CD in an Ashkenazi Jewish (AJ) population indicated a rare IL-23R R381Q variant was more frequent among AJ controls than among AJ CD patients (7% vs 2%, respectively), indicating a significant reduction in CD risk for carriers (Venegas et al 2008;Yu et al 2012). The association of this particular variant SNP with a decreased risk of CD has also been confirmed in pediatric populations (Dubinsky et al 2007) and in a large UK database studied by the Wellcome Trust (see Burton et al 2007). There are different frequencies of R381Q variants in populations of patients with various immune-mediated diseases and, thus, in control groups in different studies.…”
Section: Role For R381q Variants In Ibd (Cd and Uc)mentioning
confidence: 95%